2007
DOI: 10.1086/512981
|View full text |Cite
|
Sign up to set email alerts
|

Peakwide Mapping on Chromosome 3q13 Identifies the Kalirin Gene as a Novel Candidate Gene for Coronary Artery Disease

Abstract: A susceptibility locus for coronary artery disease (CAD) has been mapped to chromosome 3q13-21 in a linkage study of early-onset CAD. We completed an association-mapping study across the 1-LOD-unit-down supporting interval, using two independent white case-control data sets (CATHGEN, initial and validation) to evaluate association under the peak. Single-nucleotide polymorphisms (SNPs) evenly spaced at 100-kb intervals were screened in the initial data set (N=468). Promising SNPs (P<.1) were then examined in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
125
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(132 citation statements)
references
References 57 publications
(60 reference statements)
6
125
0
Order By: Relevance
“…rs11881940T was observed to be a protective factor for CAD; this allele may alter a conserved adenine in a putative interferon-regulatory factor-1-binding site, affecting the incidence of CAD. Connelly et al (2006), studying a Caucasian population, found that the alleles rs3803 and rs2713604 of the transcription factor GATA2 (Wang et al, 2007) CAD. We observed that rs3803 was a CAD-protective factor.…”
Section: Discussionmentioning
confidence: 99%
“…rs11881940T was observed to be a protective factor for CAD; this allele may alter a conserved adenine in a putative interferon-regulatory factor-1-binding site, affecting the incidence of CAD. Connelly et al (2006), studying a Caucasian population, found that the alleles rs3803 and rs2713604 of the transcription factor GATA2 (Wang et al, 2007) CAD. We observed that rs3803 was a CAD-protective factor.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CDGAP properties are well conserved between human and mouse species, and CDGAP may play an unexpected role in apoptosis and has suggestive association with coronary artery disease. 36,37 In the present study, SLC4A4 at position 4q21 showed maternal transmissions, and this gene encodes a sodium bicarbonate cotransporter involved in the regulation of bicarbonate secretion and absorption and intracellular pH. Mutations in this gene are associated with cystic fibrosis.…”
Section: Discussionmentioning
confidence: 56%
“…These polymorphisms are located in ROPN1, ROPN1-KALRN intergenic region and in the 5Ј region of the KALRN gene. In our dataset, all of these polymorphisms are also haplotype tagging SNPs, with the exception of rs7613868 and rs12637456 (SNPs 7 and 9, respectively, in Wang et al 2007) which are in almost complete LD (r 2 = 0.97; Fig. 1).…”
Section: Resultsmentioning
confidence: 90%
“…We Wrst tested the association with IS of the 12 SNPs (Table 2), originally found associated with CAD in the CATHGEN initial dataset (SNPs 2, 3, 4, 7, 8, 9, 12, 14, 20, 22, 31, and 37 in Wang et al 2007), which includes the rs4234218 (SNP 31 in Wang et al 2007) associated with cardiovascular risk, T2D, and MS (Rudock et al 2008). These polymorphisms are located in ROPN1, ROPN1-KALRN intergenic region and in the 5Ј region of the KALRN gene.…”
Section: Resultsmentioning
confidence: 99%